Exchanging traditional pumping unit for a "Geron" hydraulic drive. (November 2019) - Drozdov, A N; Blokhin, S A; Pak, D X; Zemlianskii, G S; Yurtov, M P; Antonenkova, A Y
Abstract: This work was devoted to analysis of the efficiency of the application of a "Geron" hydraulic drive as an alternative to a beam pumping unit. The issue of replacement old drives for new one was considered in the context of economic profitableness taking into account field conditions of Russia and neighbor countries. To prepare this scientific article, different data about field experience of usage the machines in different countries and fields were asked for and obtained. Thanks to information got general characteristics of both machines with their advantages and disadvantages based generally on technological, energetical and economic data were composed. After this the drives were compared with each other. As a result, hydraulic drive "Geron" was taken to be a good alternative of traditional pumping unit.